Anti-Müllerian hormone and polycystic ovary syndrome: assessment of the clinical pregnancy rates in in vitro fertilization patients. (May 2013) - Sahmay, Sezai; Guralp, Onur; Aydogan, Begum; Cepni, Ismail; Oral, Engin; Irez, Tulay
Abstract Objective: The purpose of this study is to investigate the role of serum anti-Müllerian hormone (AMH), follicle-stimulating hormone (FSH) and antral follicle count (AFC) for the prediction of clinical pregnancy rates (CPR) in women with polycystic ovary syndrome (PCOS) undergoing IVF treatment. Design: Prospective cohort study. Setting: University hospital. Patients: One hundred and fifty consecutive women with PCOS. Interventions: All women underwent controlled ovarian stimulation with long agonist protocol followed by IVF procedure. Outcomes of pregnant and non-pregnant groups were compared. Main outcome measure: CPR; AMH, FSH and AFC means and percentiles. Results: Fifty-one (34%) clinical pregnancies were observed in 150 women. Mean AMH was 6.7 ± 2.8 and 7.1 ± 4.3 ng/mL in pregnant and non-pregnant women, respectively (p = 0.594). The CPR were 27.8%, 35.0% and 37.8% in <25%, 25%–75% and >75% AMH percentiles, respectively (p = 0.656). There were also no significant difference in mean FSH and AFC between pregnant and non-pregnant women (p = 0.484 and p = 0.165, respectively). Conclusion: AMH, FSH and AFC are not predictive for CPR in women with PCOS undergoing IVF treatment. Mean AMH values were not significantly different between pregnant and non-pregnant women. Although CRP increased in parallel with the raise in AMH percentiles, this remained insignificant.